Telescopic overdenture as an alternative rehabilitation for the loss of several anterior teeth due to traffic accidents - Subiakto, Birgitta Dwitya Swastyayana; Kresnoadi, Utari (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Telescopic overdenture is a prosthesis consisting of a primary coping, or an inner crown, that is attached to a supporting tooth in the oral cavity, and a secondary coping, or an outer crown, attached to a denture, which must be compatible with the primary coping. Purpose: The purpose of this study was to restore function and aesthetics and uplift the psychological status of the patient by fabrication of a fixed removable prosthesis using the existing abutment teeth as a telescopic overdenture. Case: A 36-year-old female came to the Prosthodontic RSGM UNAIR speciality clinic on her own volition to make front dentures for her upper and lower jaws after a traffic accident one and a half years ago. The patient had an arch bar installed two months after the accident, which was removed after two months. The patient wanted new dentures to improve both her ability to eat and her appearance. Case Management: Preliminary treatments performed were; maxillary and mandibular scaling and root planing; crown lengthening of tooth 15; extraction of teeth 16, 41, 42, and 43; and alveolectomy of the mandibular anterior region. Before the definitive treatment to improve the aesthetic appearance could be carried out, the first step was to make maxillary and mandibular transitional dentures. These were to be used while waiting for healing to occur, following the socket preservation in the mandibular area. Then, for the definitive restoration, we used telescopic overdenture for the maxilla and a removable partial denture for the mandible. Conclusion: Telescopic overdenture is recommended for patients who need good aesthetics for anterior tooth loss. Telescopic overdenture uses double crowns as the retentive elements, which give better aesthetic results compared to clasps, thereby improving the psychological status of the patient. In addition, they have better retention and stability compared to conventional complete dentures.